Shameful and shameless: projecting triumph and humiliation in the Brexit Era: a psychosocial-group methodological approach - Yates, Candida (Interdisciplinary applications of shame/violence theory, 2022)
This chapter explores data emerging from a series of reflective psychosocial group-based explorations of emotional experiences of “Leavers” and “Remainers” that were held in an English coastal town following the result of the Brexit referendum in 2016. We propose that the group method deployed in that project enabled an intimate insight into underlying structures of feeling constituting psychosocial and political life in the UK from 2016–2018. Specifically, the work of the groups highlights powerful psychosocial dynamics related to a lack of emotional containment including prevalent expressions of “shame” as theorised by James (Gilligan, Violence: Reflections on a national epidemic, Vintage Books, 1996; Gilligan, Violence: Reflections on our deadliest epidemic, Jessica Kingsley Publishers, 1999; Gilligan, Social Research: An International Quarterly 70:1149–1180, 2003). We draw on these conceptualisations, and complementary psychoanalytic and cultural-philosophical accounts of shame and guilt (Akhtar, Shame, Routledge, 2018; Benedict, 1946) further support our analytic approach. The chapter examines the ramifications of the winner/loser outcome structured into the referendum-as-political mechanism, one at risk of becoming firmly instituted in post-Brexit politics.